Mechanism study of the role of biofilm played in sewage corrosion of mortar. (10th March 2018) - Kong, Lijuan; Liu, Chun; Cao, Mengfan; Fang, Jun
Highlights: The biofilm developed on mortar can act as a barrier against sewage corrosion. The porosities of biofilms decrease with the increase of sewage concentration. In ordinary sewage the thinner biofilm offers less protection on mortar corrosion. Dense biofilms play major role in protecting mortar from intensified sewage corrosion. Abstract: The artificially intensified sewage was prepared to simulate and accelerate the microbial corrosion of concrete in sewer, and the changes in weight of mortar with and without biofilm in sewage were investigated comparatively, as well as the microbial structure and activities of biofilm developed on mortar surface. Furthermore, the influence mechanism of biofilm on mortar deterioration was analyzed based on grey correlation. The results show that the biofilm developed on mortar can act as a barrier against sewage corrosion to varying degrees. The biofilm growing in sewage with chemical oxygen demand (COD) of 3000 mg/L has the most significant protective effect on mortar, which can be attributed to its high pH and dense structure. For specimens in ordinary sewage, the biofilm thickness plays the major role, especially in the first month, whereas that in sewage with too high concentration, the increasing corrosives reduced the protection of biofilm to mortar in later period.